Sharing Based Peer Group Support on Dietary Compliance of CKD Patients Undergoing Hemodialysis - Anndy Prastya; Fitria Wahyu Aryanti; Atikah Fatmawati (Jurnal Kesehatan dr. Soebandi, 2024)
Patients consume inadequate food intake from the diet recommended for Chronic Kidney Disease (CKD) patients on the one hand and excess intake of phosphorus, sodium, calcium, and potassium on the other. The purpose of this research is to know the influence sharing-based peer group support on dietary compliance of CKD patients undergoing hemodialysis in the Hemodialysis Room. The research design was quasy-experimental with approach two group pre-post test design. Technique sampling which is used was proportionate stratified random sampling with a total sample of 54 people with CKD undergoing hemodialysis. Measuring tool used was a CKD patient dietary compliance questionnaire. This research was conducted in January 2023. This study showed the score of dietary compliance in the control group pre test shows that 63% of respondents have high compliance and post test the results obtained 81% of respondents have high compliance. In the experiment groups pre test found 55.6% respondents had moderate compliance, and post test found 63% respondents had high compliance. The results of the independent t tes found that there was no difference in the score of dietary compliance after the intervention was given between two group (p value 0.716 > α = 0,05). There is no influence sharing-based peer group support on dietary compliance of CKD patients undergoing hemodialysis in the Hemodialysis Room. Thus, it is suggested that the hospital devise a plan of health education activities at least once a week, so that it can improve their health status and how to prevent severity during treatment.